Differentiation of autoimmune pancreatitis from pancreatic cancer remains challenging - Dickerson, L. D.; Farooq, A.; Bano, F.; Kleeff, Jörg H.; Baron, R.; Raraty, M.; Ghaneh, Paula; Sutton, R.; Whelan, P.; Campbell, F.; Healey, P.; Neoptolemos, John P.; et al. (World journal of surgery, 2019)
Background Autoimmune pancreatitis (AIP) is an uncommon form of chronic pancreatitis. Whilst being corticosteroid responsive, AIP often masquerades radiologically as pancreatic neoplasia. Our aim is to appraise demographic, radiological and histological features in our cohort in order to differentiate AIP from pancreatic malignancy. - Methods Clinical, biochemical, histological and radiological details of all AIP patients 1997-2016 were analysed. The initial imaging was re-reviewed according to international guidelines by three blinded independent radiologists to evaluate features associated with autoimmune pancreatitis and pancreatic cancer. - Results There were a total of 45 patients: 25 in type 1 (55.5%), 14 type 2 (31.1%) and 6 AIP otherwise not speciﬁed (13.3%). The median (IQR) age was 57 (51-70) years. Thirty patients (66.6%) were male. Twenty-six patients (57.8%) had resection for suspected malignancy and one for symptomatic chronic pancreatitis. Three had histologically proven malignancy with concurrent AIP. Two patients died from recurrent pancreatic cancer following resection. Multidisciplinary team review based on radiology and clinical history dictated management. Resected patients (vs. non-resected group) were older (64 vs. 53, p = 0.003) and more frequently had co-existing autoimmune pathologies (22.2 vs. 55.6%, p = 0.022). Resected patients also presented with less classical radiological features of AIP, which are halo sign (0/25 vs. 3/17, p = 0.029) and loss of pancreatic clefts (18/25 vs. 17/17, p = 0.017). There were no differences in demographic features other than age. - Conclusion Despite international guidelines for diagnosing AIP, differentiation from pancreatic cancer remains challenging. Resection remains an important treatment option in suspected cancer or where conservative treatment fails.
Gesehen am 25.07.2019